The Challenge of the Skin-Electrode Contact in Textile-enabled Electrical Bioimpedance, Measurements for Personalized Healthcare Monitoring Applications - Seoane, Fernando; Marquez, Juan Carlos; Ferreira, Javier; Buendia, Ruben; Lindecrantz, Kaj (IntechOpen, 2011)
None